Corporate Social Responsibility Disclosure on Companies Listed in IDX Index - NSS, RR Lulus Prapti; Triyani, Dian; Kusumawati, Citra Andriani (Management Analysis Journal, 2021)
The research is to analyze the affect of Profitability, Leverage and Industry Age, on CSR disclosure in industries listed in the IDX index. The information on the amount of industry research using purposive sampling procedures, obtained from 12 unchanged industries, is listed in the IDX index for the period 2014-2019. The research used is multiple linear regression analysis as well as panel information approach tested through Eviews 10 with fixed effect model to test hypotheses. The results of the research show profitability as well as leverage, most do not affect the CSR disclosure, as well as the age of the industry affects CSR disclosure.